SAFETY OF INTERFERON BETA 1A FOR A SUBCUTANEOUS ADMINISTRATION IN CHILDREN AND ADOLESCENTS WITH DISSEMINATED SCLEROSIS - O.V. Bykova; A.N. Platonova; N.V. Gol'tsova; L.M. Kuzenkova; A.N. Boiko ("Paediatrician" Publishers LLC, 2008)
The onset of disseminated sclerosis occurs in childhood and juvenile age in 10% of patients. nevertheless, all immunomodulatory drugs for a treatment of this disease intended for adult population of patients, and there's an age limitation to the administration of these medications. There's only one interferon beta in group of «changing the clinical course of disseminated sclerosis medications», that was annotated to the administration in patients from 16 years. It's interferon betab1a (Rebif) for subcutaneous administration in 22 ?g and 44 ?g dosage. This drug was well known as an effective and safe medication for a long term administration for a long time in adult neurological practice. But doctors have to use interferon betab1a «off label» yet in patients younger 16 years in Russia and in other countries, comparing risk of changing the regimen of age limitation and risk of deprivation of un derbaged patient of years of qualitative life.Key words: children, disseminated sclerosis, interferon beta 1a, treatment.